2019
DOI: 10.22201/facmed.20075057e.2019.29.1758
|View full text |Cite
|
Sign up to set email alerts
|

Calidad de sueño, síntomas de insomnio y rendimiento académico en estudiantes de medicina

Abstract: Introducción: La calidad de sueño y los síntomas de insomnio pueden afectar habilidades para trabajar o aprender. La licenciatura de médico cirujano, incluye gran cantidad de contenido teórico y memorístico. Los trastornos del sueño pueden alterar el rendimiento académico. Tabaco, alcohol, drogas, edad, obesidad, hormonas y otros factores biológicos, mentales, ambientales y sociales pueden incrementar la mala calidad de sueño y la incidencia de síntomas de insomnio. Los universitarios son una población vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
1
4
0
14
Order By: Relevance
“…The present study evidenced that, of the 204 students surveyed from the professional school of Nursing of the San Antonio Abad National University of Cusco, 84.3% presented a poor quality of sleep; These results are similar to the investigations carried out by Ojeda P. where 94.06% of the students had poor sleep quality (Ojeda et al, 2019), likewise, Mendez found that 70% had poor sleep quality. (Méndez & Parra, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…The present study evidenced that, of the 204 students surveyed from the professional school of Nursing of the San Antonio Abad National University of Cusco, 84.3% presented a poor quality of sleep; These results are similar to the investigations carried out by Ojeda P. where 94.06% of the students had poor sleep quality (Ojeda et al, 2019), likewise, Mendez found that 70% had poor sleep quality. (Méndez & Parra, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Each component has a score range of 0–3; 0 indicates no difficulty whereas three indicates sever sleep difficulty. The global PSQI score, ranging from 0 to 21, is the sum of all the component scores, and a higher score indicates a lower quality of sleep (Ojeda-Paredes et al, 2019). A score of ≥5 is cut-off point to differentiate good from bad sleepers (Ojeda-Paredes et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The global PSQI score, ranging from 0 to 21, is the sum of all the component scores, and a higher score indicates a lower quality of sleep (Ojeda-Paredes et al, 2019). A score of ≥5 is cut-off point to differentiate good from bad sleepers (Ojeda-Paredes et al, 2019). In the present study, Cronbach’s alpha for the PSQI was 0.89.…”
Section: Methodsmentioning
confidence: 99%
“…Principal components analysis biplot of the correlation between days of isolation, insomnia, trait of worry, coping strategies and academic engagement. previously described for Latin American undergraduate students (Durán-Agüero et al, 2019;Nunes et al, 2018;Ojeda-Paredes et al, 2019).…”
Section: Figurementioning
confidence: 99%